Monitoring for Nutrition Results in ICDS: Translating Vision into Action - Adhikari, S. K.; Bredenkamp, C. (2012)
This article focuses on the Integrated Child Development Services (ICDS), India's largest nutrition and early child development programme. It describes the political, organisational and technical challenges to building and sustaining an outcomes-oriented approach to nutrition monitoring in India. We show that the environment is conducive to strengthening nutrition programme monitoring and evaluation. Political commitment is growing, financial allocations have increased and there have been a number of reforms to strengthen the ICDS monitoring systems, but weaknesses remain. The article analyses seven technical challenges to improving the outcomes-orientation of ICDS and suggests steps that could be taken to improve monitoring.